The NLRP3 Inflammasome as a Critical Actor in the Inflammaging Process - Maria Sebastian-Valverde; Giulio M. Pasinetti (Cells, 2020)
As a consequence of the considerable increase in the human lifespan over the last century, we are experiencing the appearance and impact of new age-related diseases. The causal relationships between aging and an enhanced susceptibility of suffering from a broad spectrum of diseases need to be better understood. However, one specific shared feature seems to be of capital relevance for most of these conditions: the low-grade chronic inflammatory state inherently associated with aging, i.e., inflammaging. Here, we review the molecular and cellular mechanisms that link aging and inflammaging, focusing on the role of the innate immunity and more concretely on the nucleotide-binding oligomerization domain (NOD)-like receptor family pyrin domain containing 3 (NLRP3) inflammasome, as well as how the chronic activation of this inflammasome has a detrimental effect on different age-related disorders.